T3 levels and thyroid hormone signaling - Salas-Lucia, Federico; Bianco, Antonio C. (Frontiers in Endocrinology, 2022)
The clinical availability of tissue-specific biomarkers of thyroid hormone (TH) action consti-tutes a “holy grail” for the field. Scientists have investigated several TH-dependent markers, including the tissue content of triiodothyronine (T3)—the active form of TH. The study of ani-mal models and humans indicates that the T3 content varies among different tissues, mostly due to the presence of low-affinity, high-capacity cytoplasmic T3 binding proteins. Nonetheless, given that T3 levels in the plasma and tissues are in equilibrium, T3 signaling is defined by the intracellular free T3 levels. The available techniques to assess tissue T3 are invasive and not clinically applicable. However, the tracer kinetic studies revealed that serum T3 levels can ac-curately predict tissue T3 content and T3 signaling in most tissues, except for the brain and pituitary gland. This is true not only for normal individuals but also for patients with hypo or hyperthyroidism⸺but not for patients with non-thyroidal illness syndrome. Given this direct relationship between serum and tissue T3 contents and T3 signaling in most tissues, clinicians managing patients with hypothyroidism could refocus attention on monitoring serum T3 lev-els. Future clinical trials should aim at correlating clinical outcomes with serum T3 levels.